Effect of rescue fractional microablative CO2 laser on symptoms and sexual dysfunction in women affected by vulvar lichen sclerosus resistant to long-term use of topic corticosteroid: a prospective longitudinal study. Issue 4 (April 2020) - Pagano, Tiziana; Conforti, Alessandro; Buonfantino, Cira; Schettini, Francesco; Vallone, Roberta; Gallo, Alessandra; Avino, Luisa; Alviggi, Carlo; De Placido, Giuseppe; Sopracordevole, Francesco
Abstract: Objective: The objective of this study was to evaluate the efficacy of rescue fractional microablative CO2 laser treatment in women with severe symptoms and sexual dysfunction related to lichen sclerosus not responsive to long-term ultra-potent topical corticosteroid treatment. Methods: Consecutive eligible women with lichen sclerosus referred to our unit who received fractional microablative CO2 laser treatment after failure of ultra-potent topical corticosteroid treatment were enrolled in the study. The diagnosis was confirmed by histological assessment in all cases. Patients underwent two cycles of CO2 laser every 30 to 40 days. The severity of lichen sclerosus-related symptoms, sexual function, and procedure discomfort were evaluated with a visual analog scale in the same individual at baseline, after completion of each treatment cycle. Follow-up visits were scheduled during each treatment cycle and at least 1 month after completion of the treatment. The Friedman ANOVA test was used to evaluate differences in the visual analog scale scores of each symptom during treatment. Results: A total of 100 patients with vulvar lichen sclerosus were screened, 40 of whom fulfilled the eligibility criteria. We found a significant improvement in vulvar itching (χ 2 [2] = 31, 182, P  < 0.001), vulvar dryness (χ 2 [2] = 40, 364, P  < 0.001), superficial dyspareunia (χ 2 [2] = 37, 488, P  < 0.001), and sensitivity during intercourse (χ 2 [2] = 22, 143, P  < 0.001) after two CO2 laser cycles. Pain related to probe movement and laser application was low and did not change significantly consequent to treatment. No systemic or local adverse effects occurred during or after laser treatment. Conclusion: Fractional microablative CO2 laser treatment is safe and might represent an effective rescue procedure for patients suffering from lichen sclerosus who fail to respond to long-term ultra-potent topical corticosteroid treatment. These preliminary findings require further study with adequately powered randomized controlled trials.